Penjaminan Mutu Pendidikan Islam: Studi Sekolah MAN Insan Cendekia Serpong - Dwi Kartika Susanti; Dede Rosyada; Iswan; Ahmad Suryadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The aim of this research is to determine and evaluate the current quality assurance system for Islamic education at MAN Insan Cendikia Serpong. MAN Insan Cendikia Serpong, one of the leading educational institutions in Indonesia, is famous for its curriculum which combines Islamic principles with science and technology. To determine the elements that support the quality assurance of teaching at this institution, this research uses a qualitative methodology combined with library techniques. Data was collected using document analysis and observation. Research findings show that the success of quality assurance at MAN Insan Cendikia Serpong is supported by several key factors, including an integrated curriculum, school management, professionality, and active participation of students and parents. These findings provide important insights for the development of qualityy and sustainable islamic education policy.